Effect of complement Factor H on antibody repertoire and protection elicited by meningococcal capsular group B vaccines containing Factor H binding protein - Peter T. Beernink (Taylor & Francis Group, 2020)
Bacteria produce surface ligands for host complement regulators including Factor H (FH), which allows the bacteria to evade immunity. Meningococcal Factor H binding protein (FHbp) is both a virulence factor and a vaccine antigen. Antibodies to FHbp can neutralize its function by inhibiting binding of FH to the bacteria and confer robust complement-mediated protection. However, in the presence of human or primate FH, antibodies to FHbp do not inhibit FH binding and the protective antibody responses are decreased. This immune suppression can be overcome by modification of the FHbp antigen to decrease FH binding, which modulates the antibody repertoire to inhibit FH binding and increase protection. When FHbp is present at sufficient density on the bacterial surface, two or more antibodies can synergize to activate the complement system. Thus, modification of FHbp antigens to decrease FH binding expands the anti-FHbp antibody repertoire and increases the potential for synergistic activity.